A Buddhist Love Story: The Buddha and Yaśodharā. (30th November 2020) - Sasson, Vanessa
Abstract : This article argues that a love story between the Bodhisatta and his wife may be read into the early hagiographies. The academic study of Buddhist literature has not given romantic love much consideration. There are exceptions, but for the most part, emphasis on renunciation has trumped interest on romance. And yet, if we consider the Buddha's hagiography, romantic love proves to be a significant feature of the story. This article does not provide historical analysis of specific texts, but rather seeks to explore a number of South Asian hagiographies as a literary genre in the hopes of demonstrating Yaśodharā's important role therein. Although she is abandoned by the Bodhisatta as he makes his Great Departure, the Yaśodharā of South Asian hagiography cannot be defined by her abandonment. She is regularly represented as a powerful character with a voice of her own — one who challenges, cries, speaks, and commands. But above all else, the Yaśodharā of many of these sources is regularly described as the Buddha's match.